Meroterpene-like compounds derived from β-caryophyllene as potent α-glucosidase inhibitors. Issue 48 (5th December 2018) - Ma, Shuang-Jiang; Yu, Jie; Yan, Da-Wei; Wang, Da-Cheng; Gao, Jin-Ming; Zhang, Qiang
Abstract : Tween four meroterpene-like compounds were synthesized by combining natural moieties, which provide a new class of inhibitors against α-glucosidase. Abstract : Meroterpenoids isolated from guava ( Psidium guajava ) and Rhodomyrtus tomentosa possess special skeletons which incorporate terpenoids with phloroglucinol derivatives. Most of these meroterpenoids showed high cytotoxicity against cancer cell lines. However, their chemical diversity is very limited. Herein, we employed a biomimetic hetero-cycloaddition starting from ortho -quinone methides and an abundant natural product, β-caryophyllene, to generate meroterpene-like compounds. Considering that the source plant has hyperglycemic functions, α-glucosidase was selected as a target for bioassay. Nine compounds were screened out for promising activities (IC50 < 15 μM), which were better than the positive controls genistein and acarbose. The best inhibitor12 (IC50 2.73 μM) possesses two caryophyllene moieties. They represented a new type of skeleton possessing activities against α-glucosidase. The kinetic study exhibited that these inhibitors belong to a non-competitive type. All these inhibitors may provide an opportunity to develop a new class of antidiabetic agents.